Correlation of Femoral Tunnel Length with Body Height, Limb Length, and Thigh Length in Indian Patients Undergoing Anterior Cruciate Ligament Reconstruction. (December 2016) - Gupta, Ravi; Malhotra, Anubhav; Kumar, Pawan; Masih, Gladson David
Purpose: To measure the femoral tunnel length created through a far medial portal and determine its correlation with body height, limb length, and thigh length in 404 Indian patients undergoing anterior cruciate ligament (ACL) reconstruction. Methods: 364 male and 40 female Indian patients aged 18 to 51 (mean, 26.8) years underwent ACL reconstruction by a single surgeon using the hamstrings tendon autograft. Their body height, limb length, and thigh length were measured by a single assessor, as was the femoral tunnel length. Results: The mean femoral tunnel length was 34.5 mm. It was <30 mm in 28 patients and <25 mm in 2 patients. The correlation coefficients of the femoral tunnel length with body height, limb length, and thigh length were 0.485 (p<0.0001), 0.426 (p<0.0001), and 0.304 (p<0.0001). No patient had posterior wall blowout fracture. Conclusion: The femoral tunnel length positively correlated with body height, limb length, and thigh length in 404 Indian patients.